Priorities of Infrastructural Development and Responses of Authorities in Udaipur City, Rajasthan - Chaplot, Barkha; Shamshad, (National Geographical Journal of India, 2022)
The present paper is an attempt to analyse the priorities of infrastructural development perceived by household population and responses of authorities for the development in Udaipur city. The study is based on primary source of data generated through a comprehensive field survey in the city carried out during 2014. The boundary of the ward has been taken as the smallest unit for data collection while boundary of the zone was taken for spatial data analysis. The overall analysis of the present study reveals that more than one-third household population considered the responses of officers of Municipal Corporation, UIT, Traffic and Wards as good while nearly fifty percent households were dissatisfied with their works and responses. Further, only twenty percent households were satisfied with the responses and works of MLAs and MPs. Moreover, the households observed that the government should focus mainly on the sewerage management, solid waste management and potable water supply in the city; consequently household population has given the priority ranks to them as first, second and third respectively.